ANALISIS INFORMASI ANATOMI PADA REKONSTRUKSI MAXIMUM INTENSITY PROJECTION (MIP) DENGAN VARIASI SLICE THICKNESS PADA PEMERIKSAAN CT ANGIOGRAFI KEPALA DENGAN KASUS TUMOR OTAK - Fransisca Palupi Julanita; Siti Masrochah; Soesilo Ardi Wibowo (JRI (Jurnal Radiografer Indonesia), 2019)
Background : The existence of differences in the selection of slice thickness in the reconstruction of Maximum Intensity Projection (MIP) in the cerebral artery in some hospitals that may affect the anatomical information will require appropriate slice thickness adjustment to obtain anatomical information on CT Angiography examination in the case of brain tumor. The aim of this research is to know the difference of anatomical information on reconstruction of MIP of cerebral artery with variation of slice thickness and to find optimal slice thickness to produce anatomical information on CT Angiography examination with brain tumor case. Methods:This type of research is quantitative with an experimental approach, using a sample of 8 patients. In each patient reconstruction of cerebral artery MIP with 5 mm, 10 mm, 15 mm, 20 mm, 25 mm and 30 mm slice thickness was used. Then the results of the cerebral artery image were assessed by 3 radiologists who subjectively assessed the anatomical information by filling out the prepared questionnaires to determine the exact slice thickness that resulted in a clear cerebral artery anatomy information. Data analysis was done by Friedman test using SPSS Results: From this research can be concluded that Ho is rejected and Ha accepted which means there is difference of anatomical information on MIP reconstruction with variation of slice thickness at CT examination of head angiography with brain tumor case with value of p value < 0,001. Friedman test yields mean rank value at 30 mm slice thickness is 21,31 able to show the picture of cerebral artery that is ACA, MCA and PCA clearly when compared with slice thickness which is 5 mm, 10 mm, 15 mm, 20 mm and 30 mm. As for SOL on MIP reconstruction less clear in showing its picture with mean value value 12.00. Conclusion:CT examination of head angiography in tumor cases in MIP reconstruction should be used for 30 mm slice thickness. And to see SOL, CT Angiography head examination should use MPR reconstruction. Keywords: Maximum Intensity Projection (MIP), cerebral artery, slice thickness, CT Angiography head